Internalization of Caregiver Istikharah in Cultural Management of Islamic Education Organizations - Suyono, Suyono (Journal of Islamic Education, 2024)
This research aims to find out how the istikharah of Islamic boarding school caregivers influences the organizational culture in Islamic boarding schools. Qualitative descriptive research methods were used with a case study approach at the Nurul Abror Al-Robbaniyin Banyuwangi Islamic Boarding School. Subjects were taken from leaders, staff, teachers and students. Data collection uses interview techniques, observation and document analysis. Data analysis uses theme analysis and content analysis. The results of data analysis show that istikharah plays an essential role in shaping policy, with caregivers as the highest authority. With a long history, these cultural organisations have made significant contributions to the advancement of Islamic education in these institutions. The internalization of Istikharah among caregivers is a substantial process that combines spiritual values with daily school operations. This process begins with istikharah prayer, followed by reflection and interpretation of the results, which become the basis for decision-making. This institution's steadfast commitment to aligning its operations with Islamic principles through Istikharah is visible in its organizational culture and overall function in Islamic education.